2018
DOI: 10.1093/cercor/bhx349
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic Spontaneous Activity Mediates the Age-Related Decline in Somatosensory Function

Abstract: Sensory gating is a neurophysiological process whereby the response to a second stimulus in a pair of identical stimuli is attenuated, and it is thought to reflect the capacity of the CNS to preserve neural resources for behaviorally relevant stimuli. Such gating is observed across multiple sensory modalities and is modulated by age, but the mechanisms involved are not understood. In this study, we examined somatosensory gating in 68 healthy adults using magnetoencephalography (MEG) and advanced oscillatory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 58 publications
(78 reference statements)
2
63
0
Order By: Relevance
“…; Spooner et al . ). However, whether these frequency‐specific somatosensory cortical oscillations are modulated by haptic exploration remains unknown.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Spooner et al . ). However, whether these frequency‐specific somatosensory cortical oscillations are modulated by haptic exploration remains unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, it has recently been shown that these neural oscillations are modulated across a broad frequency range (e.g. 10-75 Hz) following a pair of identical and successive peripheral somatosensations Wiesman et al 2017;Spooner et al 2018). However, whether these frequency-specific somatosensory cortical oscillations are modulated by haptic exploration remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This weakened response to stimuli presented in rapid succession is thought to reflect the brain’s capacity to filter irrelevant information to preserve neural resources for more behaviorally relevant stimuli ( Adler et al, 1982 , 1998 ; Cromwell et al, 2008 ; Nagamoto et al, 1989 , 1991 ; Venables, 1964 ). SG has been examined in many clinical populations and across multiple sensory modalities (e.g., auditory and somatosensory) and broadly is known to be aberrant in aging, as well as many psychiatric and neurological conditions (e.g., schizophrenia, bipolar disorder, cerebral palsy, neuroHIV ( Brinkman and Stauder, 2007 ; Cheng et al, 2015a ; Cheng et al, 2016a ; Cheng et al, 2015b ; Cheng and Lin, 2013 ; Kisley et al, 2003 ; Kurz et al, 2017 ; Light and Braff, 1999 ; Spooner et al, 2018 ; Spooner et al, 2019 ; Thoma et al, 2017 )). Historically, SG paradigms have used a paired-stimulus presentation design, whereby pairs of auditory tones or electrical stimulations are administered in close temporal proximity to evaluate gating in the auditory or somatosensory domain, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio approach is the most common as it is less affected by individual differences in response amplitude across both stimulations. Importantly, regardless of the tested modality or clinical population, aberrations in SG are thought to reflect alterations in functional inhibitory processing ( Cheng et al, 2016b ; Cromwell et al, 2008 ; Gao et al, 2013 ; Spooner et al, 2018 , 2019 ), making the application of such protocols in human neurophysiology extremely desirable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation